Le 1 %, de la faculté des sciences de Paris à l’Université Pierre et Marie Curie : inventaire, restauration, valorisation d’un patrimoine artistique méconnu - Annette Roche (In Situ)
The artistic 1 %, from the Paris Sciences faculty to UPMC: inventory, restoring and valuation of under-valued heritage. When the Faculty of Science was built in Paris, André Malraux, then Minister for Cultural Affairs, had expressed the wish that the « artistic 1 % » (i.e. 1/100th of construction cost) be spent on a manifestation of contemporary art, setting up a permanent open air museum. The inventory of these once-neglected art works constitutes the first stage of a specific project, UPMC’s artistic patrimony now being the focus of an extensive valorisation programme, within the framework of rehabilitating the Jussieu campus.